Analisis Yuridis Kedudukan Majelis Rakyat Papua (MRP) dalam Sistem Pemerintahan Papua - Thomfi Loho; A. Zarkasi; Arfai Arfai; Adithiya Diar (Wajah Hukum, 2026)
The Papuan People's Assembly (MPR) is a cultural representation institution established within the framework of Papua's special autonomy to protect the rights of indigenous Papuans and uphold customary, religious, and women's values in regional governance. This study aims to analyze the legal standing of the MRP, the implementation of its authority, and the challenges of strengthening its role in the Papuan government system. The method used is normative legal research with a statutory, conceptual, and analytical approach. Legal materials were obtained through a literature review of relevant laws and regulations, scientific literature, and legal documents, then analyzed qualitatively through legal interpretation and juridical argumentation. The results of the study indicate that normatively, the MRP has a strategic position as a special institution that functions to provide consideration, approval, and protection for the rights of indigenous Papuans. However, in practice, the implementation of its authority has not been optimal due to its consultative nature, overlapping institutional relations, limited capacity, and the influence of politics and regional expansion policies. This study concludes that strengthening the role of the MRP requires regulatory refinement, increased institutional capacity, strengthened independence, and the establishment of more effective coordination so that the goals of special autonomy in Papua can be realized in a just and democratic manner.